2018
DOI: 10.3133/ofr20121024n
|View full text |Cite
|
Sign up to set email alerts
|

Geologic framework for the national assessment of carbon dioxide storage resources—Atlantic Coastal Plain and Eastern Mesozoic Rift Basins

Abstract: For an overview of USGS information products, including maps, imagery, and publications, visit https://store.usgs.gov. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the U.S. Government. Although this information product, for the most part, is in the public domain, it also may contain copyrighted materials as noted in the text. Permission to reproduce copyrighted items must be secured from the copyright owner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…The Southeast has greater potential for forestry biomass due to both the rate of growth and forested areas, but the sequestration potential is mostly in saline aquifers. Once exception may be carbonate mineralization in buried mafic rocks associated with Mesozoic rift basins . Moreover, this study did not consider the potential for storage in geologic units not observed at the surface, and the majority of rift basins are buried beneath coastal plain sediments, requiring additional detailed geophysical surveys to estimate the total storage capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Southeast has greater potential for forestry biomass due to both the rate of growth and forested areas, but the sequestration potential is mostly in saline aquifers. Once exception may be carbonate mineralization in buried mafic rocks associated with Mesozoic rift basins . Moreover, this study did not consider the potential for storage in geologic units not observed at the surface, and the majority of rift basins are buried beneath coastal plain sediments, requiring additional detailed geophysical surveys to estimate the total storage capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Once exception may be carbonate mineralization in buried mafic rocks associated with Mesozoic rift basins. 24 Moreover, this study did not consider the potential for storage in geologic units not observed at the surface, and the majority of rift basins are buried beneath coastal plain sediments, requiring additional detailed geophysical surveys to estimate the total storage capacity. The Pacific NW has significant sequestration potential but a more costly biomass supply than the Southeast.…”
Section: Discussionmentioning
confidence: 99%